(untitled) (Revista Espinhaço, 2025)
Diamantina (MG) attracts tourists with its mountains, trails, and waterfalls, located in bathers’ areas developed on metasedimentary rocks, predominantly quartzites of varied compositions, which belong to the Espinhaço Supergroup and Macaúbas Group. These areas are controlled by fracture systems oriented in the N-S, NW-SE and E-W directions. These attractions may present hazards due to the instability of rocky masses. For this reason, this study qualitatively classifies the hazard levels in these areas. The methodology included geomechanical characterization of the rocks and their discontinuities, identification of evidence of geodynamic processes and analysis of scenarios with imminent mass movement. A total of 23 balnearies were analysed, of which 15 were classified as having low geological hazard, 2 moderate, 4 high, and 2 very high. It is emphasized that this analysis has a temporal nature, as the conditions of the balnearies change over time, requiring continuous monitoring. The results are highly relevant for the region as management tools, assisting in the implementation of actions aimed at mitigating and controlling geological hazards, such as signaling hazard scenarios to visitors.